Characterization of the interaction and cross-regulation of three Mycobacterium tuberculosis RelBE modules. - Min Yang (Public Library of Science (PLoS), 2010)
RelBE represents a typical bacterial toxin-antitoxin (TA) system. Mycobacterium tuberculosis H37Rv, the pathogen responsible for human tuberculosis, contains three RelBE-like modules, RelBE, RelFG, and RelJK, which are at least partly expressed in human macrophages during infection. RelBE modules appear to be autoregulated in an atypical manner compared to other TA systems; however, the molecular mechanisms and potential interactions between different RelBE modules remain to be elucidated. In the present study, we characterized the interaction and cross-regulation of these Rel toxin-antitoxin modules from this unique pathogen. The physical interactions between the three pairs of RelBE proteins were confirmed and the DNA-binding domain recognized by three RelBE-like pairs and domain structure characteristics were described. The three RelE-like proteins physically interacted with the same RelB-like protein, and could conditionally regulate its binding with promoter DNA. The RelBE-like modules exerted complex cross-regulation effects on mycobacterial growth. The relB antitoxin gene could replace relF in cross-neutralizing the relG toxin gene. Conversely, relF enhanced the toxicity of the relE toxin gene, while relB increased the toxicity of relK. This is the first report of interactions between different pairs of RelBE modules of M. tuberculosis.